2016
DOI: 10.1103/physrevb.93.224429
|View full text |Cite
|
Sign up to set email alerts
|

Second-order magnetic critical points at finite magnetic fields: Revisiting Arrott plots

Abstract: The so-called Arrott plot, which consists in plotting H/M against M 2 , with H the applied magnetic field and M the magnetization, is used to extract valuable information in second-order magnetic phase transitions. Besides, it is widely accepted that a negative slope in the Arrott plot is indicative of a first-order magnetic transition. This is known as the Banerjee criterion. In consequence, the zero-field transition temperature T * is reported as the characteristic first-order transition temperature. By care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…7(a)) suggest that the first (PM to FM) transition is of second order, 25 in consistence with the literaure. The change of curvature happens at around 210 K, putting the T C1 value for this pseudobinary at ∼ 210 K. However, the Arrott plots near T C2 have a tendency to have a negative slope beyond 40 K. This clearly indicates that the second (FM to AFM) transition is of first order nature 25 and that the T C2 value for this pseudobinary is ∼ 40 K.…”
Section: Resultsmentioning
confidence: 91%
“…7(a)) suggest that the first (PM to FM) transition is of second order, 25 in consistence with the literaure. The change of curvature happens at around 210 K, putting the T C1 value for this pseudobinary at ∼ 210 K. However, the Arrott plots near T C2 have a tendency to have a negative slope beyond 40 K. This clearly indicates that the second (FM to AFM) transition is of first order nature 25 and that the T C2 value for this pseudobinary is ∼ 40 K.…”
Section: Resultsmentioning
confidence: 91%
“…Also for first order transition the value of the negative slope should increase with increasing temperature which is in contrast to that observed for Y-0.0 compound where the value of the negative slope decreases. Such opposite behavior has been studied by taking into account the asymmetry of the free energy density with respect to the magnetization and it was observed that a negative slope is possible at second order phase transition with the slope value decreasing with increasing temperature [24]. Also the first order are collected under the field cooled condition in the field range of 0 -1 T by the protocol described in Ref [26].…”
Section: Resultsmentioning
confidence: 99%
“…H/M curves in Fig. 9 (k-o)) is a powerful technique to distinguish first-order phase transition from second order phase transition below Curie point (T C ) of a FM [33][34]. According to Banerjee criterion [34][35], is positive for second-order and negative for first order phase , where a competitive magnetic spin order between the low temperature surface spin order and high temperature CAFM spin order is observed in the temperature range 100 K-150 K. The spin flop field (H sf ), an important parameter for changing magnetic spin order from low magnetic state (AFM) to high magnetic state (CAFM), varied on the variation of both Cr content and measurement temperature of the A10 samples (Fig.…”
Section: Structural Propertiesmentioning
confidence: 99%